Singularidade e subjetividade : relações discursivas entre palavra e imagem na obra de Valêncio Xavier Minha mãe morrendo e o menino mentido - Oliveira, Peterson José de (2015)
This thesis aims at discussing the singularity of the book Minha mãe morrendo e o menino mentidoby Valêncio Xavier, taking into account that the way the relationship between the verbal and the visual happens can offer a singular output for the subject who, in this post-modernity, keeps a deadly enjoyment with the visual. In order to do so, we seek thetheory developed by Jacques Lacan to define singularity, which led us to address concepts such as subject and enjoyment, as well as the notion of sinthome. We have analyzed the author\'s relationship with one of his fundamental artistic strategies, montage, understood as a form of sublimation. The montage would bethe equivalent of a sinthomewhose task would be of linking the three registers (Imaginary-Symbolic and Real). Bearing that in mind, we have shown how the visual and the verbal in the work analyzed is in opposition to a socially widespread enjoyment, which emphasizes the imaginary aspects of the subject\'s relation with the visual. Images and words, far from having a complementary relationship between themselves, indicate a constant point of problematization to what concerns such a relation. In order to reflect on the forms of relationship between the verbal and the visual forms, we have also used Jacques Rancière s ideas whose theoretical assumptions helped us understand the concept of montage and its transformation throughout history. The ideas developed by Vladimir Safatle about the sublimation in Lacan was also of our interest. Thus, the analysis of Minha mãe morrendo e o menino mentidosupports the idea that in the relationship with the visual and the verbal, the montage is the way the subject finds to produce meaning and anenjoyment of his own. Thus, we went over the chapters of the thesis, scanning themes and the structure of the book by using the concepts alluded before: singularity, synthome, sublimation, and enjoyment. We have found that Valêncio met a complex and unique way of using the visual because, there, the subject does not submit himself to an imaginary way of dealing with traumatic or pleasurable visual experiences lived in childhood. By (re)living the impact of images to which he was subjected in childhood, Valêncio transformed the deadly power of images such as the dying mother or the severed heads of Lampeão s gang into a singular work. Therefore, Minha mãe morrendo e o menino mentidosuggests a creative alternative for the plethora of images to which the subject, especially nowadays, is submitted: he can make use of signifiers that come from the Other and find, beyond a meaning, his own way of enjoyment. Even though art is not the only way to subvert the surplus scopic enjoymentpresent in our contemporary world, Valêncio Xavier indicates a possible way: to work with the fragments of verbal and visual discourse that crossed his life in order to produce a meaning and an enjoyment of his own.